2000
DOI: 10.1029/1998je000624
|View full text |Cite
|
Sign up to set email alerts
|

A thermal emission spectral library of rock‐forming minerals

Abstract: Abstract. A library of thermal infrared spectra of silicate, carbonate, sulfate, phosphate, halide, and oxide minerals has been prepared for comparison to spectra obtained from planetary and Earth-orbiting spacecraft, airborne instruments, and laboratory measurements. The emphasis in developing this library has been to obtain pure samples of specific minerals. All samples were hand processed and analyzed for composition and purity. The majority are 710-1000/am particle size fractions, chosen to minimize partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
297
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(310 citation statements)
references
References 21 publications
10
297
1
2
Order By: Relevance
“…All mirrors in the system are gold coated and flat to one-fourth wavelength in the visible wavelengths, making them excellent reflectors in the infrared, with reflectivity >0.995 over nearly the entire spectral range [52]. Furthermore, in principle the optical design of this system is quite similar, with the exception of the microscope objective and the relay optics required to achieve the ∼85 μm measurement spot size, to that of a suite of existing emission spectrometers used extensively by the planetary science community to evaluate and characterize data returned from spacecraft missions [29,31,37,38,41,42,45,[53][54][55][56].…”
Section: Optical Designmentioning
confidence: 93%
See 2 more Smart Citations
“…All mirrors in the system are gold coated and flat to one-fourth wavelength in the visible wavelengths, making them excellent reflectors in the infrared, with reflectivity >0.995 over nearly the entire spectral range [52]. Furthermore, in principle the optical design of this system is quite similar, with the exception of the microscope objective and the relay optics required to achieve the ∼85 μm measurement spot size, to that of a suite of existing emission spectrometers used extensively by the planetary science community to evaluate and characterize data returned from spacecraft missions [29,31,37,38,41,42,45,[53][54][55][56].…”
Section: Optical Designmentioning
confidence: 93%
“…At this scale, there is no compositionally/ mineralogically uniform surface; rather, endmembers in the thermal infrared spectral range (e.g., 6-100 μm), to first-order, add linearly with aerial abundance [39]. It is possible to use a linear unmixing model for thermal infrared emission spectroscopy, where an endmember library of pure minerals [40,41] is used as a reference to determine quantitative mineral abundances based on their respective contributions (using a linear least squares method) to the measured spectrum. This method has been used extensively in the laboratory to determine the bulk compositions of unknown samples [42] and on spacecraft data to characterize the composition of Earth and other planetary bodies, including Mars [31,36,[43][44][45].…”
Section: B Vibrational Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of the optical properties of snow found both a minimum and a maximum in the imaginary index of refraction in the far infrared leading to surface emissivities with a range of values from 0.96 to 0.99 depending on grain size (25,26), with significant implications for the infrared radiation budget (27). In support of the Mars Global Surveyor Thermal Emission Spectrometer, Christensen et al (28) developed a library of emissivities of pure mineral samples indicating diverse spectral structure of common surficial minerals at wavelengths from 15 μm to 25 μm with values as low as 0.8. Glotch et al (29) and Glotch and Rossman (30) found similarly low values of far-IR emissivity for Martian surfaces.…”
Section: Significancementioning
confidence: 99%
“…There are several important spectral library projects that have been established recently in this area of research such as the U.S. Geological Survey (USGS) spectral library [6], the Arizona State University (ASU), Thermal Emission Spectral Library [7], the ASTER spectral library [8], Specchio [4], the DLR spectral archive [9], and the globally distributed soil spectral library ICRAF-ISRIC (World Agroforestry CentreInternational Soil Reference and Information Centre) [10]. These spectral libraries provide a large amount of standard spectral data and remote sensing image extraction of spectral endmembers.…”
Section: Introductionmentioning
confidence: 99%